The master-piece of love songs A dialogue betwixt a bold keeper and a lady gay, who woo'd his lord's daughter, and carried the day; But soon after marriage was forc'd for to fight with his lord and six gentlemen for his own right; he cut them, and hevv'd them, and paid them with blovvs, and made them his friends, that before vvere his foes. To the tune of, A week before Easter,&c. (Printed for T. Norris, at the looking-glass on London-bridge. And sold by J. Walter, at the hand and pen in High Holborn, 1650)
bb A love ballad about a man who wooed and won his lord's daughter.
Not in Wing; But cf. Wing M1065, M1064.
Date of publication surmised by cataloger from other works from these publishers.
Verse - "It was a bold keeper"
Reproduction of original in the Bodleian Library.
Keywords: Broadsides -- England -- London -- Early works to 1800.; Songs, English -- Texts -- Early works to 1800.; Love songs -- Early works to 1800.; Ballads -- England -- between the 17th and 18th century.